Acetophenone derivatives from the root bark of Cynanchum wilfordii as potential neuroprotective agents. (April 2018) - Jiang, Hao-Wen; Lin, Jing; Wang, Gui-Min; Zhang, Jing-Jing; Gu, Shan-Shan; Cao, Lei; Chen, Yan; Wang, Ling; Jiao, He; Zhu, Wei-Liang; Zhang, Hai-Yan; Zhao, Wei-Min; et al.
Graphical abstract: Highlights: Seven new acetophenones were isolated form Cynanchum wilfordii (Maxim.) Hemsl. Each racemate was separated into individual enantiomers by chiral HPLC. ECD calculations were used to assign the enantiomers' absolute configurations. (+)-3 and (−)-3 showed neuroprotective effects on Aβ-treated SH-SY5Y cells. Abstract: Seven new acetophenone derivatives, three couples of enantiomers (±)-cynwilforones D −  F (1  −  3 ) together with cynwilforone G (4 ), were isolated form the root bark of Cynanchum wilfordii (Maxim.) Hemsl. Their structures were deduced based on spectroscopic analysis and X-ray crystallography. Each racemate was separated into individual enantiomers, and electronic circular dichroism (ECD) calculations were used to assign their absolute configurations. All compounds exhibited inhibitory effect of A β oligomerization in different degrees. Among them, (+)-3 and (− )-3 showed neuroprotective effects on A β oligomers-treated SH-SY5Y cells.